Health literacy profiles correlate with participation in primary health care among patients with chronic diseases: a latent profile analysis - Xu, Qi; Wang, Baokai; Zhang, Li (Frontiers in Public Health, 2025)
BackgroundGiven the persistent, complex, and diverse health needs of chronic disease patients, their health literacy and active participation in the process of primary health service delivery has gained increasing attention. This study aimed to identify the potential profiles of patient health literacy, examine the sociodemographic and health factors associated with these profiles, and investigate the relationship between health literacy profiles and patient participation in primary health care (PHC).MethodsA multistage stratified sampling method was adopted to conduct a cross-sectional questionnaire survey of 911 patients with chronic diseases in Shandong Province, China, between July and August 2023.ResultsThree distinct latent profiles were identified: low health literacy group (10.98%), moderate health literacy group (56.86%), and high health literacy group (32.16%). Age, marital status, residency, occupational status, education level, personal monthly income, and health status had statistically significant effects on patient health literacy profiles (p < 0.05). Patients with higher health literacy exhibited significantly greater participation in PHC than those with lower health literacy (B = 3.544, p < 0.001).ConclusionThis study’s findings underscore the need for tailored interventions to enhance patient health literacy. In addition, the findings offer valuable insights for enhancing health literacy in facilitating patient participation in PHC.